Analisis Kepemimpinan Rasulullah Dalam Perspektif Pendidikan Agama Islam - Aminudin S, Muh. Dzihab; Sasmita, Mitra; Haerudin, Haerudin; Rahma Dilla Zainuri; Al-Amin, Al-Amin (Jurnal Ilmiah Global Education, 2024)
The biggest crisis in the world today is the crisis of example or uswah. The need for a leader who has character like the Prophet Muhammad is very necessary because many people who serve as leaders do not have the character that a leader should have in terms of educational leadership. Leadership is the characteristic of a leader in assuming formal moral and legal responsibility for all the implementation of his authority which has been delegated to the people he leads. As an exemplary leader who is an ideal model of leadership, Rasulullah was gifted with four main characteristics, namely: Sidiq, Amanah, Tablighi and Fathonah. Sidiq means honest in words and deeds, amanah means being trustworthy in maintaining responsibilities, tablig means conveying all kinds of goodness to the people and fathonah means being intelligent in managing society